Consumer Protection in Electronic Commerce Reviewed from the Aspect of Contractual Liability in Marketplace Platforms - Anatomi Muliawan; Desrina Tiara Maharani (SENTRI: Jurnal Riset Ilmiah, 2026)
Electronic commerce through marketplaces is rapidly growing, offering convenience in transactions but also creating challenges in consumer protection. Consumers remain vulnerable due to asymmetric information, differences in geographic location, limitations of liability clauses in marketplace terms, and difficulties in accessing evidence. This study aims to analyze: (1) Consumer protection regulations in electronic commerce under Law Number 8 of 1999 concerning Consumer Protection, and (2) The contractual responsibility of marketplaces in safeguarding consumers. Using normative legal research with statutory and conceptual approaches, the study analyzes data qualitatively through literature review. The results indicate that while the Consumer Protection Law provides normative rightssuch as information, safety, and compensation the law is not fully adapted to digital transactions, leaving gaps in enforcement and remedies. Marketplaces, as intermediaries, hold contractual responsibility through mechanisms like complaint handling, refunds, and product returns. However, limitations of liability and unclear procedures for exercising consumer rights create legal uncertainty and weaken consumer protection. The study concludes that these gaps should be addressed by strengthening and clarifying marketplace contractual responsibilities, ensuring effective, fair, and legally certain protection for consumers in electronic commerce.